The cardiovascular and functional consequences of arteriovenous fistula formation in chronic kidney disease - Korsheed, Shvan (2011)
Background. Native arteriovenous fistula (AVF) is the vascular access of choice and its use c.f. catheters is associated with sustained reduction in mortality. This may be due to factors beyond dialysis catheter associated sepsis. This study aims to investigate the impact of AVF formation on the spectrum of cardiovascular factors that might be important in the pathophysiology of cardiovascular diseases in CKD patients.